2011
DOI: 10.1200/jco.2011.36.6799
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Study of Erlotinib in Combination With Placebo or R1507, a Monoclonal Antibody to Insulin-Like Growth Factor-1 Receptor, for Advanced-Stage Non–Small-Cell Lung Cancer

Abstract: PurposeR1507 is a selective, fully human, recombinant monoclonal antibody (immunoglobulin G1 subclass) against insulin-like growth factor-1 receptor (IGF-1R). The strong preclinical evidence supporting coinhibition of IGF-1R and epidermal growth factor receptor (EGFR) as anticancer therapy prompted this study.Patients and MethodsPatients with advanced-stage non–small-cell lung cancer (NSCLC) with progression following one or two prior regimens, Eastern Cooperative Oncology Group (ECOG) performance status 0 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
110
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 23 publications
4
110
0
2
Order By: Relevance
“…The IGF-IR and ErbB3 signaling pathways have been implicated as potential escape pathways in cancers exhibiting resistance to targeted therapies and chemotherapies (18)(19)(20)(21)(41)(42)(43)(44)(45). We demonstrate that the IGF-IR pathway is often coactivated with ErbB3, another nonoverexpressed receptor.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The IGF-IR and ErbB3 signaling pathways have been implicated as potential escape pathways in cancers exhibiting resistance to targeted therapies and chemotherapies (18)(19)(20)(21)(41)(42)(43)(44)(45). We demonstrate that the IGF-IR pathway is often coactivated with ErbB3, another nonoverexpressed receptor.…”
Section: Discussionmentioning
confidence: 82%
“…We have previously shown that direct targeting of ErbB3 is optimal for blocking the ErbB3-PI3K cascade (32). Recent clinical strategies have combined IGF-IR inhibitors with EGFR-based therapies resulting in disappointing outcomes (19)(20)(21). We propose that the simultaneous blockade of IGF-IR and ErbB3 is necessary to maximize the potency of PI3K/ AKT/mTOR inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-treatment concentration of IGF-1 in serum [12,13], expression of IGF-1R in tumours, the level of circulating IGF-2 and IGF-binding proteins [12] have all been evaluated as predictors for response to IGF-1R targeting therapy in clinical trials. It was found that the level of membranous IGF-1R expression has a correlation with response rate to therapy using the antibody CP-751,871 [15].…”
Section: Discussionmentioning
confidence: 99%
“…Reports from clinical trials emphasize that identification of predictive biomarkers and careful patient stratification are required for successful IGF-1R-targeted treatment [11][12][13]. Pre-clinical data demonstrated that a higher level of membranous IGF-1R is associated with response to IGF-1R inhibitors [14].…”
Section: Introductionmentioning
confidence: 99%